The discrepancy between perceived importance and adequacy in discussing topics related to pregnancy and birthing in maternity services: the views of mothers giving birth in Northern Greece - Lavdaniti, Maria; Raftopoulos, Vasilios; Sapountzi-Krepia, Despina; Psychogiou, Maria; Tsiligiri, Maria; Vehvilainen-Julkunen, Katri (My University, 2010)
Aim: To explore aspects of maternity care regarding mode of delivery, preferred mode and place for next delivery, number of abortions, and the discrepancy between perceived importance and adequacy in discussing topics related to pregnancy and birth in maternity services. Background: Childbearing has been highly medicalized in Greece; deliveries are taking place in hospitals under the supervision of obstetricians.Methods: A convenience sample of 607 mothers (mean age 33.1±5.8) who had given birth one week to one year prior to the study participated and completed the Kuopio Instrument for Mothers.Results: Out of 607 eligible subjects, 46.8% (n=284) completed the KIM after first delivery and 52.7% (n=320)after second or multiple deliveries; 9.1% (n=55) reported preterm delivery and 22.7% (n=138) one or more abortions. The majority, 66.3 % (n=403), had vaginal delivery, while 32.9% (n=200) had caesarean section (CS). A total of 485 mothers (81.5%) reported that they preferred to have their next delivery in a hospital, and 298 (49.8%) visited private obstetricians for pregnancy monitoring. The discussion of CS in maternity clinics(p=0.001) was rated as more important by women who had undergone CS, while recovery after delivery (p=0.050) and normal course of pregnancy (p=0.014) were rated as not adequately discussed during their last pregnancy.Conclusions: there is a need for further research in order to obtain information on these important issues at a national level.
Keywords: Greece; Mothers; Pregnancy; Prenatal care